Noise Enhanced Logic Gates - Sinha, Sudeshna (American Institute of Physics, 2011)
It was observed recently that, when one drives a two‐state system with two square wave as input, the response of the system mirrors a logical output (NOR∕OR). The probability of obtaining the correct logic response is controlled by the interplay between the noise‐floor and the nonlinearity. As one increases the noise intensity, the probability of the output reflecting a NOR∕OR operation increases to unity in a window of moderate noise, and then decreases to zero again for very large noise. This concept of noise enhanced logic gate performance under optimal noise was called: Logical Stochastic Resonance (LSR). Here we review this concept of Logical Stochastic Resonance and provide details of suitable electronic circuit systems demonstrating LSR. We also review the extension of this approach to realize logic gates with Coherence Resonance Systems (LCR).
Only IISERM authors are available in the record.